THE EFFECT OF WRITTEN CORRECTIVE FEEDBACK ON HIGHER EDUCATION STUDENTS’ WRITING ACCURACY - Kisnanto, Yustina Priska (Universitas Pendidikan Indonesia, 2016)
AbstractWith the higher demand of accuracy on students’ writing in university level, the present study examines the effect of direct and indirect written corrective feedback (WCF) on students’ L2 writing accuracy. The study was conducted in a six-week period with 43 Indonesian university student participants majoring IT. The results of the pre- and post-writing tests showed that 1) the writing accuracy improvement of the students receiving direct WCF was statistically significant while the writing accuracy improvement of the students given the indirect WCF treatment was not; 2) the accuracy improvement in the untreatable error rate of the direct WCF group was the most significant compared to all types of error in both WFC student groups. The study concludes that considering the students’ current English proficiency level and learning setting with limited English exposure, written corrective feedback, especially the direct one, helps the university students improve their writing accuracy.Keywords: corrective feedback, L2 writing, higher education